2019
DOI: 10.1021/acs.inorgchem.9b00984
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Regulation in Carbon Monoxide (CO) Release: Anion Responsive CO-Releasing Molecule (CORM) Derived from (Terpyridine)phenol Manganese Tricarbonyl Complex with Colorimetric and Fluorescence Monitoring

Abstract: A new CO-releasing terpyridine based manganese­(I) tricarbonyl complex, [MnBr­(CO)3(terpy-C6H4OH)] (1·Mn-OH) functioning via light has been reported. For the first time, we have demonstrated the allosteric regulation concept to control the CO-releasing properties of a CO-releasing molecule (CORM). Fluoride ion is reported to function as an allosteric activator to control the rate of CO release in the CORM. Complex 1·Mn-OH represents an interesting new class of CO-releasing system that releases CO upon irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…1165 This system was used as an in vivo magnetic-resonance-imaging contrast reagent. Allosteric regulation of CO release was demonstrated in complex 248a (Table 16), 1166 in which the phenolic substituent of the terpyridyl ligand responds to fluoride ions by undergoing deprotonation, leading to allosteric activation of CO release; the deprotonated complex released CO approximately 1 order of magnitude more efficiently than its neutral form. Ford and co-workers synthesized another terpyridine-based manganese tricarbonyl complex 248b (Table 16), which can release CO both by 1-photon excitation in the visible region and also by 2photon excitation at 750 and 800 nm because the terpyridine ligand acts as an efficient 2-photon antenna.…”
Section: Photorelease Of Gasotransmittersmentioning
confidence: 99%
“…1165 This system was used as an in vivo magnetic-resonance-imaging contrast reagent. Allosteric regulation of CO release was demonstrated in complex 248a (Table 16), 1166 in which the phenolic substituent of the terpyridyl ligand responds to fluoride ions by undergoing deprotonation, leading to allosteric activation of CO release; the deprotonated complex released CO approximately 1 order of magnitude more efficiently than its neutral form. Ford and co-workers synthesized another terpyridine-based manganese tricarbonyl complex 248b (Table 16), which can release CO both by 1-photon excitation in the visible region and also by 2photon excitation at 750 and 800 nm because the terpyridine ligand acts as an efficient 2-photon antenna.…”
Section: Photorelease Of Gasotransmittersmentioning
confidence: 99%
“…One way round this is to use a substituted species that absorbs in the visible such as (CO) 5 ReMn(CO) 3 (phenanthroline) 7 which under deep-red photolysis splits the Re-Mn bond to give mononuclear radicals; normally these would simply recombine but in oxygenated media, species are formed which are much more labile towards CO release. In another example, MnBr(CO) 3 (L) (L = phenol substituted terpyridyl), 8 the rate of photorelease can be regulated through deprotonation by F À that red-shifts the absorption dramatically. A different approach is to use a palladium porphyrin as a photosensitiser which on absorption at 635 nm converts to the excited triplet state, 3 Pd(porph)*; the latter transfers energy to Mn 2 (CO) 10 exciting it to a photolabile triplet state, releasing CO. 9 This is intriguing because almost all photochemistry of metal carbonyls occurs from excited singlet states and triplet sensitisation is a rarity.…”
Section: Previous Reviews and Applications Of Metal Carbonyl Photoche...mentioning
confidence: 99%
“…CORMs can be activated by various external stimuli: change of solvent, presence of enzymes, thermal, pH or light variations, and oxidation . Among metal-CORMs, a terpyridine-containing Mn­(I) complex was found to be able to release CO under the control of blue light irradiation, while two Ru­(II) complexes, with bipyridines ligands functionalized with amides and an alkyne functionality or a green-fluorescent BODIPY (boron-dipyrromethene) dye, were found to be quickly internalized with accumulation at the endoplasmic reticulum and mitochondria . Interestingly, it has been demonstrated that CO can modulate the cleavage of human islet amyloid polypeptide (hIAPP) and beta-amyloid (Aβ) production by decreasing BACE1 expression, reducing Aβ levels and improving memory deficits in Alzheimer’s disease (AD) transgenic mice .…”
Section: Introductionmentioning
confidence: 99%